The Relationship between Halal Practices and Financial Performance among F&B Service Industry in Batu Pahat - Pakhruddin, Ummi Nurain; Kamaruddin, Nor Kamariah (Research in Management of Technology and Business, 2025)
F&B restaurants service industry is one contributor to Malaysia’s halal business. There are three research objectives in this study mainly about examine the level of financial performance among F&B restaurant services in Batu Pahat. Secondly, examine the level of halal practices among F&B restaurant services in Batu Pahat. Lastly, examine the relationship between halal practices and financial performance among F&B restaurant services in Batu Pahat. However, many industries focused less on their organizations’ financial success and only focus more on how their operational procedures. Also, there are industries that did not receive a halal certificate due to being unable to achieve an effective performance management halal standard. Next, difficulty to the certification management procedure due to ineffective communication between managerial level. The researcher conducted quantitative research approach by using questionnaire to collect data. The study responses rate is 99.38% of 160 respondents through a questionnaire using two data with analyzed using SPSS software. The result showed a negative weak relationship (r= -0.112). The findings revealed that mean score very highly correlation analysis indicated a negative relationship between two independent variables which are Halal and thoiyyib and IHC while the staff shown weak relationship with the financial performance among F&B service industry in the Batu Pahat. The results of this study can also be used by policymakers and regulatory bodies to assess the effectiveness of Halal certifications and standards, providing guidance for enhancing the regulatory environment in the F&B industry.